OPERATIONAL STRATEGY AND PERFORMANCE RECOVERY AT PT LAUT BONTANG BERSINAR (LBB) BONTANG - Muthia Indah Permatasari; Ramlawati; Mahfudnurnajamuddin (Journal Informatic, Education and Management (JIEM), 2026)
PT Laut Bontang Bersinar (LBB) is a regional company responsible for managing Loktuan Port in Bontang, East Kalimantan. In recent years, the company has faced complex and multidimensional operational challenges, covering financial, human resource, infrastructure, and governance aspects. The main problems include fixed contribution arrears to the Bontang City Government of IDR 450 million, delays in employee salary and holiday allowance (THR) payments, and suboptimal maintenance of port facilities such as spotlight lamps and CCTV systems. Amid these challenges, the company gained trust through a two-year port management contract extension from the Class II Bontang Port Authority and Harbormaster Office (KSOP), which also became a critical momentum for operational transformation. This study aims to analyze the operational management strategies implemented by PT LBB in efforts to recover company performance, especially after leadership changes and the signing of a new contract, and to evaluate the effectiveness of the 100-day recovery plan launched by the new board of directors. The research method used is a qualitative case study approach with secondary data analysis techniques derived from trusted media coverage from May 2024 to March 2025, official company documents, and previous community service reports involving PT LBB. The findings reveal that PT LBB implemented a recovery strategy based on comprehensive internal audit, operational cost efficiency of up to 10%, gradual port infrastructure improvements, and restructuring of the financial reporting system. As highlighted by Sudirman et al. (2023) regarding the importance of discipline in reporting and contribution payments, this study also found that non-compliance in fiscal obligations has worsened the company's financial crisis. The operational recommendations proposed include implementing Internet of Things (IoT)-based information technology for real-time monitoring of port facilities, strengthening collaboration with all stakeholders, and preparing a sustainable master plan for the port (RIP) aligned with regional spatial planning. This study is expected to provide academic and practical contributions in the form of an operational recovery model for regional port companies experiencing similar crises.